DEVELOPING THE PROFESSIONALISM OF TEACHERS THROUGH KELOMPOK KERJA GURU (KKG) IN CLUSTER I OF ELEMENTARY SCHOOL - fitri Fadhila; hasan bisri (Fakultas Agama Islam dan Pendidikan Guru, 2018)
The low quality of teachers caused to several factors, is the low education level of teachers, teachers didn’t depth understand the substance of science teacher, majority of teachers profession is only usual routine without regard the values of education for students. Developing the professionalism of teachers can improve teacher competencies order have positive impact in learning process. On the professionalism developing program do that through KKG. The research’s goal to describe the developing and efforts of teachers in improving the professional competence through KKG. This research used qualitative approach and case study.Data collected through observation, interviews, questionnaires, and documentation study. Analysis technical of data is reduction, display, verification, and conclusion. Result showed elementary school of teachers Cluster I Sub Ciawi have good professional competence. Aspects that played information about professionalism competence, is the participation teachers in KKG’s program. KKG program is related to improvement of the professional competence teachers is training for creating lesson plans, syllabi, modules, ICT, PTK and the others